2013
DOI: 10.1001/jamaoto.2013.1324
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Adenoidectomy vs Initial Watchful Waiting Strategy in Children With Recurrent Upper Respiratory Tract Infections

Abstract: trialregister.nl Identifier:NTR968; isrctn.org Identifier:ISRCTN03720485.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…Despite the limitations of a single center (Tuscany is recognized as a region with excellent patient care in the Italian scenario) retrospective analysis, our data evidence the difficulties in the recognition of PFAPA syndrome and in the appropriate management of PFAPA patients. Additionally, by comparing the costs of our cohort of patients with those ones derived from common diseases of childhood, emerged that PFAPA patients have a higher economic costs compared to conditions including asthma, atopic disease, recurrent respiratory infections, and celiac disease (2225). On the contrary, the direct cost for a patient with juvenile idiopathic arthritis (JIA) is markedly higher, as expected (2628).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the limitations of a single center (Tuscany is recognized as a region with excellent patient care in the Italian scenario) retrospective analysis, our data evidence the difficulties in the recognition of PFAPA syndrome and in the appropriate management of PFAPA patients. Additionally, by comparing the costs of our cohort of patients with those ones derived from common diseases of childhood, emerged that PFAPA patients have a higher economic costs compared to conditions including asthma, atopic disease, recurrent respiratory infections, and celiac disease (2225). On the contrary, the direct cost for a patient with juvenile idiopathic arthritis (JIA) is markedly higher, as expected (2628).…”
Section: Discussionmentioning
confidence: 99%
“…day care, parental leave of absence). We adjusted for inflation using the consumer price index 3,16,17 . Compared to an initial watchful waiting policy, the differences in societal costs for adenotonsillectomy and adenoidectomy were €324 (ie €252 plus 28.5% inflation from 2002 to 2017) and € 608 (ie €541 plus 12.3% inflation from 2009 to 2017), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…27 In 2011, a trial on this topic reported similar outcomes, and higher healthcare and societal costs, for adenoidectomy compared to watchful waiting. 11,28,29 During an international consensus conference in 2017 on the management of otitis media with effusion (OME), it was advised that adenoidectomy only be performed in children aged over four years who suffer from OME with symptomatic adenoid hypertrophy. 30 In 1984, specific indications for tonsillectomy in children with severe tonsillitis were defined, known as the Paradise criteria, and international consensus was reached on this topic.…”
Section: Changes In Indications For Tonsil Surgery In Childrenmentioning
confidence: 99%